Comparison of infrared thermography of the face between mouth-breathing and nasal-breathing children - Valentim, Amanda Freitas; Motta, Andréa Rodrigues; Silva, Júlia Ana Soares; Furlan, Renata Maria Moreira Moraes; Porto, Matheus Pereira; Becker, Helena Maria Gonçalves; Franco, Letícia Paiva; Gama, Ana Cristina Côrtes (European archives of oto-rhino-laryngology, 2025)
Purpose To compare the temperature of thermoanatomic points and areas of the upper and lower lips between mouth-breathing and nasal-breathing children. Methods This cross-sectional observational study had a sample of 30 nasal-breathing and 30 mouth-breathing children aged 4 to 11 years. One front-view, one left-view, and one right-view infrared thermogram of the face were acquired from each participant. A total of 14 thermoanatomic points plus the upper lip and lower lip areas were marked on the front-view thermograms, while on the side-view thermograms, six thermoanatomic points were marked. The research also calculated the difference between the temperature of the upper and lower lip areas (∆T area) and between the temperature of the points on the upper and lower lips (∆T points). The normalized mean temperatures of points and areas and temperature differences were compared between groups with the t-test and Mann-Whitney test. Results The temperature of the thermoanatomic points closest to the lip (nasolabial, Labial Commissure, and lower labial), areas of the lips, and external acoustic meatus was lower in mouth breathers than in nasal breathers, which did not happen for most other points. ∆T area and ∆T points were not different between the groups. Conclusion Thermography is a promising complementary diagnostic tool, since showed mouth-breathing children had lower temperatures in the region of the lips than nasal breathers.